Pseudohemangioma of the head - diagnostic difficulties in a pediatric patient with Ewing's sarcoma of the scalp: case report - Joanna Urszula Borowik; Kinga Justyna Kuśmierczuk; Wojciech Brodowski; Katarzyna Anna Kozak; Patryk Jawoszek; Agnieszka Zaucha-Prażmo (Kazimierz Wielki University, 2019)
Introduction: Ewing's sarcoma (ES) is the second most common malignant bone tumor of childhood and adolescence. Typically, ES affects the long bones, pelvis and the trunk. Primary location in the scalp is rare. Aim of study: The aim of our study is to focus on the case of a pediatric patient with Ewing's sarcoma located in the scalp, which adopted a cavernous angioma mask, and to assess the available knowledge on the diagnosis and treatment of the extracostal ES located in the scalp. Material and methods: The research method was a case study. The research material was the patient's medical record, and the technique used was an analysis. An unsystematic review of Polish and English-language scientific literature was conducted. Electronic databases: PubMed, SCOPUS and Google Scholar were searched using the keywords: sarcoma, Ewing, hemangioma, pseudohemangioma, the head, the scalp. Results: When the girl was 6 months old, a tubercle appeared on her head. It was asymptomatic, but gradually increased. Imaging studies suggested the diagnosis of cavernous hemangioma. The tumor did not respond to treatment and still was growing. A decision was made to include resection. The upward tumor underwent histopathology with immunohistochemical assessment and genetic testing. The result pointed to extraskeletal Ewing's sarcoma. Conclusions: Despite the few cases described in the literature, remember about atypical locations of primary Ewing sarcoma such as scalp. Making the right diagnosis was a challenge for the multi-specialist team of doctors. Histopathological examination supplemented by immunohistochemical assessment and genetic testing gave a definitive diagnosis and enabled proper treatment.